Allometric Equations to Estimate the Aboveground Biomass of Seedling and Sapling Plants in 10 and 20 Years Old of Secondary Forests in Sarawak, Malaysia. - Karyati, -; Isa, Ipor; Ismail, Jusoh; Mohd. Effendi, Wasli (Atlantis Press B.V, 2021)
The seedlings and saplings plant stage determines the successional stages in the secondary forest establishment process. The estimation on aboveground biomass (AGB) of seedling and sapling plants is needed to describe undergrowth contribution in the secondary forest. This study's objective was to develop allometric equations for accurate estimation of AGB for seedlings-saplings in 10 and 20 years old of secondary forests. The study was carried out at sites with two stages of the fallow period: lands with a fallow period of 10 and 20 years, respectively, in Sarawak, East Malaysia. The AGB data of all selected seedlings and saplings with the different species within 100 sample quadrates were used to develop allometric equations for seedlings and saplings in each study site. This study developed allometric equations to estimate AGB of seedlings-saplings (diameter at the ground surface of < 5 cm), particularly in 10 and 20 years of fallow ages.